EARNINGS MANAGEMENT AND PERFORMANCE: SHARIA VIS-A-VIS NON-SHARIA FIRMS - Hanafi, Rustam; Sutapa, Sutapa (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
Earnings management and firm performance are crucial issues in corporate governance, particularly in contexts where ethical considerations intersect with financial practices. This study addresses a research gap by comparing earnings management practices and performance between Sharia and non-Sharia firms in Indonesia, a country with a majority Muslim population. The study analyzes data from firms listed on the Indonesia Stock Exchange during the 2015–2021 period, comprising 2,247 observations. Using independent t-tests, the findings reveal that Sharia firms engage in significantly lower earnings management compared to non-Sharia firms. Furthermore, Sharia firms demonstrate superior performance metrics. These results highlight the potential advantages of adopting Sharia-based governance principles, suggesting that such practices contribute to higher-quality financial reporting and improved firm performance. The study underscores the importance of integrating Sharia values into corporate governance frameworks to enhance ethical and financial outcomes